Re-organization of Pacific overturning circulation across the Miocene climate optimum - Holbourn, Ann (2024)
The response of the ocean overturning circulation to global warming remains controversial. Here, we integrate a multiproxy record from International Ocean Discovery Program Site U1490 in the western equatorial Pacific with published data from the Pacific, Southern and Indian Oceans to investigate the evolution of deep water circulation during the Miocene Climate Optimum (MCO) and Middle Miocene Climate Transition (MMCT). We find that the northward export of southern-sourced deep waters was closely tied to high-latitude climate and Antarctic ice cover variations. Global warming during the MCO drove a progressive decrease in carbonate ion concentration and density stratification, shifting the overturning from intermediate to deeper waters. In the western equatorial Pacific, carbonate dissolution was compensated by increased pelagic productivity, resulting in overall elevated carbonate accumulation rates after ~16 Ma. Stepwise global cooling and Antarctic glacial expansion during the MMCT promoted a gradual improvement in carbonate preservation and the initiation of a near-modern Pacific overturning circulation. We infer that changes in the latitudinal thermal gradient and in Southern Ocean zonal wind stress and upper ocean stratification drove radically different modes of deep water formation and overturning across the MCO and MMCT.